THE CHALLENGES AND ENHANCING PROFESSIONAL COMPETENCE: AN IN-DEPTH ANALYSIS OF THE HOTEL MANAGEMENT STUDENTS DURING THE INDUSTRIAL TRAINING EXPOSURE ((PJHAS) PUSA Journal of Hospitality and Applied Sciences, 2024)
Background: Industrial training exposure allows the students to apply the theoretical knowledge gained in the  classroom to real-world situations. This practical application enhances their understanding of concepts and fosters  a deeper learning experience. Working in a real-world setting exposes students to various challenges and scenarios,  helping them develop a wide range of practical skills. Objectives: (1) To identify the various challenges encountered by  hotel management students during their industrial exposure training period. (2) To study about the impact of industrial  exposure on the acquisition of practical skills, professional demeanor, and industry-specific knowledge among hotel  management students. (3) To identify the facilities and support mechanisms offered by hotels to trainees during their  industrial exposure is crucial for understanding the learning environment and ensuring a positive and enriching  experience for the trainees. Methodology: The study is descriptive in nature. The sample for the study consists of 124  from Wayanad district, Kerala. The primary data required for the research was collected using a structured questionnaire  which was distributed off-line. Stratified Random sampling technique was used for the study. Data was analyzed based  on the category of the hotel where the training was done and the statistical analysis was based on percentage, chi square  test, correlation analysis, ANOVA Test with the help of IBM SPSS Version 23. Results: 58.1% respondents agreed  with the statement that they get benefited by doing the industrial exposure training; whereas, 17.7% strongly agreed,  13.7% of the respondents neither disagreed nor agreed, 8% disagreed and only a minority of 4% of the respondent  said that they are not benefited by doing the industrial exposure training. The relationship between the category of  the hotels and the stipend provided, weekly off and communication problems faced by the trainees had a statistically  significant linear relationship (p
Keywords: Practical Skills; Professional Demeanor; Industry-specific Knowledge